Identification of CCR5 Δ32 Allele in Different Ethnic Groups of Nepal - Shrestha, Dipendra; Shrestha, R; Sherchand, SP; Sherchan, S; Hendriksen, RS; Bhatta-Sharma, L; Bhatta, DR (Nepal Medical College Journal, 2020)
The chemokine receptor CCR5 exhibits an important role for the CD-4 mediated entry of HIV-1. Previous studies revealed that Δ32 mutation on the CCR5 gene results in truncated protein and hence confers protection against HIV-1 infection and AIDS progression, as observed in Caucasian population. However, the status of Δ32 mutation on CCR5 is still unknown in many Nepali ethnic groups though detection of heterozygous CCR5 Δ32 mutation allele has been reported from Chidimar and Thakali ethnic groups. We studied the presence of the Δ32 mutation in 300 blood samples from 11 ethnic groups of Nepal by analyzing PCR product of CCR5 gene region flanking the Δ32 mutation region. The primer set (forward -5’ CTC CCA GGA ATC ATC TTT ACC 3’ and reverse - 5’ TCA TTT CGA CAC CGA AGC AG 3’) flanks the site of the Δ32 deletion region of CCR5 gene. This results in a PCR fragment of 200 base pairs for the CCR5 wild allele and 168 base pairs for a Δ32 deletion mutation allele. All samples were found to exhibit wild type CCR5 gene; but no Δ32 mutation observed. Absence of Δ32 mutation in CCR5 gene indicates that Nepali population is not genetically resistant to HIV infection, if other genes are not considered.